2020
DOI: 10.1103/physrevd.101.104053
|View full text |Cite|
|
Sign up to set email alerts
|

Gravitational waves from hierarchical triple systems with Kozai-Lidov oscillation

Abstract: We study gravitational waves from a hierarchical three-body system up to first-order post-Newtonian approximation. Under certain conditions, the existence of a nearby third body can cause periodic exchange between eccentricity of an inner binary and relative inclination, known as Kozai-Lidov oscillations. We analyze features of the waveform from the inner binary system undergoing such oscillations. We find that variation caused due to the tertiary companion can be observed in the gravitational waveforms and en… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 79 publications
1
37
0
Order By: Relevance
“…In addition, we show that a significant fraction of the triples produced by GCs will have high eccentricity in the LISA frequency range. Works by Randall & Xianyu (2019), Hoang et al (2019), Deme et al (2020), Emami & Loeb (2020), and Gupta et al (2020) have shown the potential for LISA to be able to detect the peaks of the eKL oscillation. We also find that, since GW radiation is efficient in reducing the eccentricity of merging binaries, sub-hertz detectors such as the proposed DECIGO detector (Kawamura et al 2011) will be crucial to understand the contribution of GCs to the merger rate (see also .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we show that a significant fraction of the triples produced by GCs will have high eccentricity in the LISA frequency range. Works by Randall & Xianyu (2019), Hoang et al (2019), Deme et al (2020), Emami & Loeb (2020), and Gupta et al (2020) have shown the potential for LISA to be able to detect the peaks of the eKL oscillation. We also find that, since GW radiation is efficient in reducing the eccentricity of merging binaries, sub-hertz detectors such as the proposed DECIGO detector (Kawamura et al 2011) will be crucial to understand the contribution of GCs to the merger rate (see also .…”
Section: Discussionmentioning
confidence: 99%
“…Finally (F) triple or higher-order stellar systems can also lead to the formation of BBHs (e.g. Silsbee & Tremaine 2017;Rodriguez & Antonini 2018;Gupta et al 2020;Toonen et al 2020). Within their uncertainties, almost all of these formation channels have been shown to have rate estimates consistent or marginally consistent with the empirical LVC rates.…”
Section: Introductionmentioning
confidence: 99%
“…This can be accomplished with the detection of electromagnetic counterparts (e.g., Lee et al 2010;Tsang 2013), or through the detection of imprints on the GW waveform present with some merger channels. For instance, for some EKL-assisted mergers in GN, the gravitational pull of the SMBH on the merging binary can be detected in both LIGO and LISA due to induced GW phase shifts (Inayoshi et al 2017;Meiron et al 2017), and eccentricity variations (Hoang et al 2019;Randall & Xianyu 2019;Deme et al 2020;Emami & Loeb 2020;Gupta et al 2020).…”
Section: Discussionmentioning
confidence: 99%